SISTEM INFORMASI MANAJEMEN PENGOLAHAN DATA DI BALAI WILAYAH SUNGAI SUMATERA V KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT - Suherman, Yanni; Yadewani, Dorris DY (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
RESEARCH THAT THE AUTHOR DID IN THE SUMATRA RIVER REGION HALL V MINISTRY OF PUBLIC WORKS AND PUBLIC HOUSING OF WEST SUMATRA PROVINCE AIMS TO BUILD AN INFORMATION MANAGEMENT SYSTEM FOR DATA PROCESSING PAYING ORDERS AND FUND DISBURSEMENT WARRANTS. THE METHOD USED IS A FIELD STUDY THAT IS CONDUCTING DIRECT INTERVIEWS WITH COMMITMENT MAKING OFFICIALS OF GROUNDWATER AND RAW WATER I, THEN STUDY LIBRARIES AND LABORATORY STUDIES USING VB.NET 2013. THE RESULTS OF THE RESEARCH ARE TO FACILITATE THE DATA PROCESSING. SO THAT CONCLUSIONS CAN BE OBTAINED, WITH THIS MANAGEMENT INFORMATION SYSTEM, IT CAN FACILITATE THE PROCESSING DATA OF PAYING ORDERS AND FUND DISBURSEMENT WARRANTS TO PRODUCE INFORMATION AND REPORT MAKING CORRECTLY, QUICKLY AND ACCURATELY.